RELATIONSHIP OF URINARY HYDROXYPROLINE AND GROWTH IN CHILDREN - DR. P. KIRANMAI; DR. S. LAXMINARAYANA; DR. K. AMBIKADEVI (International Journal of Pharma and Bio Sciences, 2014)
Urinary hydroxyproline excretion reflects collagen metabolism which is more in children than in adults due to the growth phase. Present study aims to find relationship between growth and hydroxyproline excretion. Study was done in 90 children of three age groups 6-9 yrs, 10-13 yrs and 14-16 yrs who formed three study groups Group I, Group II and Group III respectively with 30 children in each group .Thirty Adults in age group of 30-40 yrs formed the control group. 24 hrs Urinary Hydroxyproline was estimated in the study and control groups. Student T test was used for statistical analysis. Statistically significant increased excretion of Hydroxyproline (p<0.01) is seen in children in age group of 10-13yrs (Group-II) when compared to control group. Among groups also statistically significant increased excretion is seen in children of 10-13 yrs age group rather than in children of 6-9 yrs and 14-16 yrs age group. In our present study there was more excretion of hydroxy proline in Group II (10-13yrs) where the growth rate is more than in age group 6-9 and 13-16 yrs where the rate of growth is less, results indicate a good correlation between growth and urinary hydroxyproline. Hence it can be used as an effective indicator of growth in children.